6p-27-53=4

Simple and best practice solution for 6p-27-53=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-27-53=4 equation:


Simplifying
6p + -27 + -53 = 4

Reorder the terms:
-27 + -53 + 6p = 4

Combine like terms: -27 + -53 = -80
-80 + 6p = 4

Solving
-80 + 6p = 4

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '80' to each side of the equation.
-80 + 80 + 6p = 4 + 80

Combine like terms: -80 + 80 = 0
0 + 6p = 4 + 80
6p = 4 + 80

Combine like terms: 4 + 80 = 84
6p = 84

Divide each side by '6'.
p = 14

Simplifying
p = 14

See similar equations:

| 5.4=t+(-6.1) | | 2(n+1.5)=4.5 | | 117.345+m=200 | | 4v^2-14v-15= | | 9x-5=2x+16 | | -58.109=v-47.736 | | 2x^2+.25x=0 | | -27-53+4=6x | | -0.08=f+0.07 | | -7(t+3)=0 | | a(2a^2+3)+(a^2-10)= | | -x=0.12 | | 6.21=e+(-3.48) | | 4x+8=2x-1 | | 4x-10=95 | | -13.8=h+15.603 | | -176=7x+4(-7x-2) | | 47+5k=9(k+3) | | 2(9-8)= | | -165=-3x+6(-x-11) | | -22=p+13.7 | | 3(x-2)+46=-2x | | k-263.48=-381.09 | | 9c-3c=-8 | | x-19.7=17.48 | | 2x+4(2x-5)=-110 | | 8-9(4-1)(3-4)= | | -4.095+b=18.665 | | 4x-10=180 | | z-81.6=-81.6 | | x+95=180 | | -3-4x=5x-3 |

Equations solver categories